The association between students' leisure activities on weekends during Movement Control Order (MCO) and demographic characteristics / Syafiza Saila Samsudin ... [et al.] - Samsudin, Syafiza Saila; Mohamad Adnan, Noor Izyan; Nik Badrul Alam, Nik Muhammad Farhan Hakim; Mohamed, Siti Rosiah; Ismail, Nazihah
A movement control order implemented by Malaysia's government due to the COVID-19 pandemic had strictly controlled the education system, where virtual classes had taken over the physical classes. This study aimed to describe the students' weekend leisure activities during the movement control order in Universiti Teknologi MARA Pahang. A simple random sampling technique was conducted by distributing online survey questionnaires to a sample of 213 students. Descriptive statistics, Chi-Square and Fisher Exact test were used in data exploration and association determination between students' activities and demographic characteristics. It was found that majority of the students did not make a weekend to-do list and slept more than four hours. Most of the females, 53% enjoyed their weekend, but 51% of males did not. From all of the students, 31% spent less than one hour with their family, while all students surfed their social media every day. The study concluded that seven activities were influenced by gender, four activities were influenced by their program, and two were influenced by their current semester.